Studi Klimograf Perubahan Cuaca dan Bangkitan Malaria di Kabupaten Banjarnegara - Raharjo, Mursid (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2003)
ABSTRACT Background : Malaria in Banjarnegara district is inequitable distribution. The fluctuate of meteorology factors was a dominant factor of the vector densities. This is very important object especially to evaluate the correlation between the climograph of meteorology data and malaria incidence. The climograph was the important instrument to predicted the re-emerging of malaria. Methods : Based on the malaria incidence and the meteorological data in ten years, the phenomena of climate change was analyzed. Correlation between malaria incidence and meteorology data analyses by the Pearson Product Moment. Climograph was composed by the average of meteorology data as long as ten years period. Average of yearly meteorology climograph was composed by the yearly meteorology data. The overlay of the two climograph conclude relationship between malaria case incidence and fluctuate of meteorology. Results : The results of the research showed coefficient of correlation rainfall to malaria incidence –0,75, correlation of air temperature to malaria incidence –0,6875, and correlation of air humidity to malaria incidence –0,6407. If the annual climograph as same as range with the average of the ten years climograph, incidence of malaria was low (1995, API 0,02). If the annual climograph different with the average of the ten years climograph in which the incidence of malaria was high (2001, API 15,53). Key : Malaria incidence, Climograph study, Re-emerging disease